If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 3x = 20 Reorder the terms: 3x + 7y = 20 Solving 3x + 7y = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 3x + 7y + -7y = 20 + -7y Combine like terms: 7y + -7y = 0 3x + 0 = 20 + -7y 3x = 20 + -7y Divide each side by '3'. x = 6.666666667 + -2.333333333y Simplifying x = 6.666666667 + -2.333333333y
| 38-3x=23 | | 3(2x+5)=-3(-3x-2) | | 9x-5=5x-17 | | x+9=-5x+3 | | 56-2x=9x+25 | | 3x+6=10x-15 | | 2x(x-3)=7(x-3) | | 7s-4=26 | | x+0.833*x=7791.56 | | 2(3x-1)+3=21 | | 2x+40-6x=2-9x+3 | | 2x^2+54x=18 | | 3x-42=5x | | 8x+7x-54=180 | | 3x+3=12x-40 | | 2x^2+27x=9 | | x+0.833x=7791.56 | | x+0.833=7791.56 | | 5x-(2x-10)=25 | | 9v-8=6v-2 | | 30x-5=25 | | 10a-2=7a+11 | | c=45+0.5(72) | | (x+1)+(x+2)-5=6 | | y(y-5)=6 | | -9(x-4)=54 | | 6y+8=3(2y+3) | | 55*75-3= | | 141-4x=32x+21 | | 10x+2(-5x)=-6 | | 5-3(2x+4)=-6x+6 | | 3(x+4)=3x+11 |